Things We Do for No Reason: Prealbumin Testing to Diagnose Malnutrition in the Hospitalized Patient. Issue 4 (31st October 2018) - Lacy, Mary; Roesch, Justin; Langsjoen, Jens
Abstract : Inspired by the ABIM Foundation's Choosing Wisely® campaign, the "Things We Do for No Reason" series reviews practices which have become common parts of hospital care but which may provide little value to our patients. Practices reviewed in the TWDFNR series do not represent "black and white" conclusions or clinical practice standards, but are meant as a starting place for research and active discussions among hospitalists and patients. We invite you to be part of that discussion.